Difficulty with Dental Caries among Adolescents Who Are Underweight: A Nationwide Study - Vinodh Bhoopathi, BDS, MPH, DScD; Paula Ortega-Verdugo, DDS, MS, PhD; Christine Wells, PhD; Honghu Liu, MS, PhD (Journal of Pediatrics: Clinical Practice)
This study highlights a unique association between weight status and difficulty with dental caries among US adolescents. Being underweight was significantly associated with dental caries in adolescents aged 10-17.